Effectiveness And Innovation Of Village Treasury Land Management In Improving The Welfare Of Orphans: A Case Study Of Sidomulyo Village, Jember Regency - Noga Riza Faisol (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
ABSTRACT Introduction: This study aims to analyze the effectiveness of Village Treasury Land (TKD) management in improving the welfare of orphans in Sidomulyo Village, Silo District, Jember Regency. The research uses a descriptive qualitative approach with a case study method. Data was collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model with a source triangulation technique to ensure the validity of the data. The results of the study showed that TKD management was carried out transparently through an annual lease auction system that generated Village Original Income (PAD) of Rp212,500,000 per year. All of these results were allocated 100% to orphan welfare programs with a composition of 50% consumptive, 25% educational, and 25% productive. The effectiveness of the program has been proven to be high, as shown by the reduction in the dropout rate from 8 cases (2022) to 1 case (2025), as well as the fulfillment of the basic needs of 161 orphans. Obstacles in the management of productive funds are overcome through institutional innovation in the form of the formation of cooperatives that manage productive businesses. Methods: The research employs a descriptive qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, andanalyzed using the Miles and Huberman model, with source triangulation applied to ensuredata validity. Results: The results indicate that TKD management is conducted transparently through an annual leaseauction system, generating Village Original Revenue (PAD) amounting to IDR 212,500,000per year. The entire revenue is allocated 100% to orphan welfare programs, with acomposition of 50% for consumptive needs, 25% for education, and 25% for productivepurposes. The program demonstrates a high level of effectiveness, as evidenced by asignificant reduction in school dropout cases from 8 cases in 2022 to 1 case in 2025, as well as the fulfillment of basic needs for 161 orphans Conclusion and suggestion: Challenges in managing productive funds were addressed through institutional innovation by establishing a cooperative that managesproductive business activities. This study concludes that TKD management based on the principles of trust (amanah) andjustice is not only socially effective but also capable of creating a sustainable economicempowerment model for vulnerable groups